Metastatic primitive neuroectodermal tumor involving testis - Kshirsagar Ashok; Langade Yogesh; Ahire Manoj; Nanivadekar Manjiri; Nikam Shashikant; Neeraj Shekhar (Wolters Kluwer Medknow Publications, 2008)
A 40-year-old male patient presented with enlarging mass over left leg region. Incisional biopsy report revealed an undifferentiated malignant round cell sarcoma, for which above-knee amputation was done. One year later, the same patient presented with left testicular swelling which appeared to be malignant. A left high orchiedectomy was done. Biopsy report showed metastatic round cell tumor, which was confirmed by immunohistochemistry as primitive neuroectodermal tumor. Metastasis to testis is very uncommon.